Efficacy of TENS Therapy, Therapeutic Ultrasound and Stabilization Splint as an Adjuvant to Pharmacotherapy for Temporomandibular Disorders - Deepak Yadav; Hemanta Raj Pathak; Ravish Mishra; Laxmi Kandel; Shahid Ali (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION This study aims to assess the effectiveness of adjunctive treatments like transcutaneous electric nerve stimulation (TENS), therapeutic ultrasound (ThUs), and stabilization splint (SS) in combination with pharmacotherapy (PT) in enhancing pain relief, mouth opening, lateral excursion, joint sound reduction, muscle tenderness improvement, and jaw deﬂection in patients with temporomandibular disorders (TMDs), affecting the temporomandibular joint and masticatory muscles. MATERIAL AND METHODS The study involved 90 patients divided into three groups. Pharmacotherapy (Tab. Myospaz) was prescribed to all patients, each group received either TENS, ThUs, or SS as adjunctive treatment. Outcomes were measured at baseline and various intervals post-treatment. RESULTS TMDs were more prevalent in younger age group (21-30 years) with female predilection (F:M =2.21:1). Signiﬁcant differences were observed in pain scores, with TENS and ThUs groups showing greater reductions compared to SS. ThUs demonstrated superior results in mouth opening, while TENS showed better outcomes in lateral excursion and muscle tenderness reduction. CONCLUSION This study concluded that both TENS and therapeutic ultrasound effectively reduced pain with therapeutic ultrasound showing better results in improving mouth opening, and TENS demonstrating better results in lateral excursion and muscle tenderness reduction. No signiﬁcant difference among three groups were found in reducing joint sounds and deviation/deﬂection.